2009
DOI: 10.1073/pnas.0908718106
|View full text |Cite
|
Sign up to set email alerts
|

miR319a targeting of TCP4 is critical for petal growth and development in Arabidopsis

Abstract: In a genetic screen in a drnl-2 background, we isolated a loss-offunction allele in miR319a (miR319a 129 ). Previously, miR319a has been postulated to play a role in leaf development based on the dramatic curled-leaf phenotype of plants that ectopically express miR319a (jaw-D). miR319a 129 mutants exhibit defects in petal and stamen development; petals are narrow and short, and stamens exhibit defects in anther development. The miR319a 129 loss-of-function allele contains a single-base change in the middle of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

15
359
1
7

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 399 publications
(382 citation statements)
references
References 36 publications
15
359
1
7
Order By: Relevance
“…In particular, great progress has been made in functional characterization of the class II TCPs in Arabidopsis. These transcription factors play important roles in leaf, flower, shoot morphogenesis, and hormone biosynthesis (Damerval et al, 2007;Koyama et al, 2007;Schommer et al, 2008;Nag et al, 2009;Guo et al, 2010). The cellular functions of class I TCPs are less well explored, but several previous studies indicated that they are involved in a number of cellular or developmental processes.…”
mentioning
confidence: 99%
“…In particular, great progress has been made in functional characterization of the class II TCPs in Arabidopsis. These transcription factors play important roles in leaf, flower, shoot morphogenesis, and hormone biosynthesis (Damerval et al, 2007;Koyama et al, 2007;Schommer et al, 2008;Nag et al, 2009;Guo et al, 2010). The cellular functions of class I TCPs are less well explored, but several previous studies indicated that they are involved in a number of cellular or developmental processes.…”
mentioning
confidence: 99%
“…In apexes, there are transcripts of both genes, which is probably associated with their participation in the regulation forming the leaves, as described in tomato (Ori et al 2007). In A. thaliana, there are three genes encoding miR319 (MIR319a, -b, -c), MIR319a and MIR319b encoding identical mature miRNA and the expression patterns for the three MIR319 genes are distinct, suggesting that these genes may have largely unique developmental functions (Nag et al 2009;Schommer et al 2012). It can therefore be assumed that other unidentified MIR319 genes also exist in I. nil that may influence the accumulation of mRNA InTCP4 in other tissues.…”
Section: Discussionmentioning
confidence: 99%
“…2a) and InMIR319 indicates a similar tissue expression pattern to MIR319a and MIR319b in A. thaliana (Nag et al 2009). The results of Nag et al (2009) suggest that miR319a/b might not play an important role in leaf development, but in petal and stamen development. In A. thaliana jaw-D mutants (overexpression of MIR319 gene) have slightly shorter hypocotyls than wildtype plants, whereas increased TCP activity leads to longer hypocotyls (Palatnik et al 2003;Schommer et al 2008;Sarvepalli and Nath 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations